Europe's ‘Horizon 2020’ science funding programme: how is it shaping up? - Galsworthy, Michael; McKee, Martin (Journal of Health Services Research & Policy, 2013)
Over the past 15 years, the European Union (EU) has spent around €80 billion on science research via Framework Programmes (FP5, FP6 and FP7). In 2014, a new programme, Horizon 2020, will likely invest another €70 billion over 6 years. Health research has been a major part: between 12% and 17% was spent on official FP5 and FP6 health research lines, although our work categorizing all EU science projects puts the health-related investment proportion nearer to 20%. Here, we compare our analyses and experiences with the European Commission's own impact assessments and plans that inform the Horizon 2020 programme. Much is moving in the right direction but some key gaps are overlooked. We discuss four areas: red tape, what to fund, harnessing informatics and neglect of Eastern Europe.